Measurement of Microplastic Release After the Use of Polypropylene Nasal Irrigation Bottles - Kyung Soo Kim; Hyun Jin Min (Clinical and Experimental Otorhinolaryngology)
Objectives. Microplastics originating from plastic materials may pose risks to human health. This study investigated the presence of microplastics in nasal irrigation fluids collected from reused bottles, focusing on the duration of bottle usage. Methods. Readily available nasal irrigation bottles made of polypropylene were purchased. Unused bottles served as controls. Test samples were prepared to simulate 1-, 3-, and 6-month reuse. Nasal irrigation fluid samples (n=12) were collected from each set of bottles: three from the new control bottles and nine from the bottles simulating 1-, 3-, and 6-month reuse. Raman spectroscopy was used to detect microplastics in the nasal irrigation samples, and the results were compared based on the duration of bottle use. Results. An average of 33.00±20.42 microplastic particles per 300 mL was detected in the nasal irrigation fluid from the control bottles. In comparison, bottles used for 1, 3, and 6 months contained averages of 68.66±30.07, 261.66±20.59, and 204.33±52.16 microplastic particles per 300 mL, respectively. The majority of these particles ranged in size from 10 to 100 μm and were primarily fragment-shaped. Polypropylene was identified as the predominant type of microplastic, suggesting it was directly released from the irrigation bottles. Conclusion. We detected microplastics in nasal irrigation fluids, which likely originated from the repeated use of nasal irrigation bottles. The quantity of microplastics was significantly higher in samples from bottles simulating 3 months of use compared to the control samples. Therefore, we recommend the development of guidelines to regulate the duration of nasal irrigation bottle usage to reduce microplastic infiltration into the body via the sinonasal cavity.